Independent Curriculum Learning Asessment at Junior High School Level - Fatihah, Siti; Istanto, Istanto (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2024)
Every change aims to create new things that lead to success. Digital assessment offers a number of advantages that can be utilized in both synchronous and asynchronous classroom contexts, with the aim of improving the implementation of assessments to be more accurate and efficient. Improving the education system, one of which is through changes to the curriculum and assessments, is expected to support the development of intelligence in the evolution of education. Assessment in the Independent Curriculum is considered an assessment function which aims to identify students' characteristics, potential and learning achievements (outcomes). This assessment is designed to directly identify students' learning needs and observe their progress in absorbing the lessons taught by the teacher. Existing learning assessment models vary greatly, and this research adopts a phenomenological approach with descriptive qualitative methods. The research results show that there are seven learning assessment models, each with different uses and functions that are adapted to the needs of students. These models provide various ways that can be used by teachers to support learning assessments according to the individual needs of students. In general, learning assessments in the Independent Curriculum can be divided into two main categories, namely formative assessments and summative assessments. This research aims to identify competency assessment models offered in the context of the Independent Curriculum. The conclusion of this research is that these assessment models play a role in supporting student development and introduce various methods that can be used in implementing student development assessments, in accordance with the objectives of the Independent Curriculum.